Liquid Biopsy-based Precision Therapy in Patients with Advanced Solid Tumors: A Real-world Experience from a Community-based Oncology Practice. (19th February 2022) - Choucair, Khalil; Mattar, Bassam Ibrahim; Van Truong, Quoc; Koeneke, Travis; Van Truong, Phu; Dakhil, Christopher; Cannon, Michael W; Page, Seth Joel; Deutsch, Jeremy Michael; Carlson, Eric; Moore, Dennis Frederic; Nabbout, Nassim H; et al.
Abstract: Background: Liquid biopsy testing offers a significant potential in selecting signal-matched therapies for advanced solid malignancies. The feasibility of liquid biopsy testing in a community-based oncology practice, and its actual impact on selecting signal-matched therapies, and subsequent survival effects have not previously been reported. Patients and Methods: A retrospective chart review was conducted on adult patients with advanced solid cancer tested with a liquid-biopsy assay between December 2018 and 2019, in a community oncology practice. The impact of testing on treatment assignment and survival was assessed at 1-year follow-up. Results: A total of 178 patients underwent testing. A positive test was reported in 140/178 patients (78.7%), of whom 75% had an actionable mutation. The actual overall signal-based matching rate was 17.8%. While 85.7% of patients with no actionable mutation had a signal-based clinical trial opportunity, only 10% were referred to a trial. Survival analysis of lung, breast, and colorectal cancer patients with actionable mutations who received any therapy ( n = 66) revealed a survival advantage for target-matched ( n = 22) compared to unmatched therapy ( n = 44): patients who received matched therapy had significantly longer progression-free survival (PFS) (mPFS: 12 months; 95%CI, 10.6-13.4 vs. 5.0 months; 95%CI, 3.4-6.6; P = .029), with a tendency towards longer overall survival (OS) (mOS: 15 months; 95%CI, 13.5-16.5 vs. 13 months; 95%CI: 11.3-14.7; P = .087). Conclusions: Implementation of liquid biopsy testing is feasible in a US community practice and impacts therapeutic choices in patients with advanced malignancies. Receipt of liquid biopsy-generated signal-matched therapies conferred added survival benefits. Abstract : Standard molecular profiling is traditionally based on tumor resection or biopsy; however, the development of liquid biopsy assays now allow for early, timely, and minimally invasive testing for circulating genetic material in the blood, including circulating tumor DNA. This article reports a real-world experience using next-generation sequencing-based liquid biopsy testing in patients with advanced solid tumors.